INSTRUCTIONAL COMPETENCE AS A PREDICTOR OF STUDENT LEARNING ENGAGEMENT - Yuliana Ginggada; Melizubaida Mahmud; Sudirman Sudirman; Meyko Panigoro; Yulianti Toralawe (Jurnal Pendidikan Ekonomi dan Bisnis, 2026)
This study investigates the relationship between teacher professional competence and student learning activity among Grade XI students at SMA Negeri 1 Bonepantai, Indonesia. While policy frameworks emphasize competence-based instruction, challenges remain in translating this into active student engagement, particularly in under-resourced contexts. Employing a quantitative descriptive–correlational design, the study gathered data from 64 respondents using validated and reliable Likert-scale instruments. Instrument testing confirmed high validity (r > 0.412) and reliability (α = 0.923 for competence and 0.922 for activity). Descriptive findings revealed high average scores for both teacher competence (4.34) and student learning activity (4.45). Regression analysis produced the model Ŷ = 24.291 + 0.730X, with a significant positive effect (t = 6.267 > t-table = 1.669; p < 0.05) and R² = 0.388, indicating that competence explains 38.8% of the variation in student activity. Strongest indicators included creative material development and student group discussions, while the lowest were contextualization and opinion expression. These findings confirm theoretical assumptions that professional competence enhances learner participation and underscore the need for CPD focused on culturally responsive and dialogic teaching. The study contributes to empirical knowledge on instructional quality in Indonesian secondary education and invites further research using multivariate approaches to examine the remaining variance in student engagement.